PENGARUH PERMAINAN WORDS IN A QUESTION TERHADAP KETERAMPILAN BERTANYA BAHASA INDONESIA SISWA KELAS V SEKOLAH DASAR - Valentina, Ishika; Kusuma, Dewi; Nurbait, Syifa (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2026)
The observations revealed that the questioning skills of fifth-grade students at SDN Pangrango, Cirebon City, were still relatively low. Approximately 93.94% of the 33 students were recorded as inactive in asking questions during learning activities. To address this issue and encourage active student engagement, the ‘words in a question’ language game was implemented. This study aimed to examine the application of the ‘words in a question’ game and determine its effect on students’ questioning skills, including the extent of improvement following its implementation. This research employed a quantitative pre-experimental design with a population of 210 students from SDN Pangrango and a sample of 33 fifth-grade students. Data analysis was conducted using IBM SPSS Statistics 25 and Microsoft Excel 2010. Questionnaire results showed a percentage score of 90%, indicating that the implementation of the ‘words in a question’ game was highly effective in improving students’ questioning skills. The paired-sample t-test yielded a significance value of 0.000, meaning 0.000 < 0.05; thus, H0 was rejected and H1 was accepted (indicating a significant effect). The average pretest score was 59%, while the posttest score increased to 80%, demonstrating improved questioning skills after the intervention. The mean N-Gain score of 0.5304 indicated a moderate improvement (medium category). Therefore, it can be concluded that the ‘words in a question’ game positively influences the Indonesian language questioning skills of fifth-grade students at SDN Pangrango, Cirebon City.